DAMPAK KEBERHASILAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. ASTRA INTERNASIONAL TERHADAP KESEJAHTERAAN MASYARAKAT - Ivendi Agustri Noviyanto; Simammora, Liska (Universitas Djuanda, 2023)
Corporate Social Responsibility (CSR) is a company's commitment to participate in economic Corporate Social Responsibility (CSR) is a company's commitment to participate in economic development that adjusts the achievement of economic performance with social and environmental performance. CSR is expected to have an impact on the welfare of the community after receiving the program from the company. Tanon Hamlet, Ngrawan Village is one of the recipients of the CSR program of PT. Astra International through the Kampung Berseri Astra (KBA) program. From the observations, the CSR program has had an impact on the community. However, there is no research that proves the truth. This study aims to: 1) knowing the implementation of the CSR program provided by PT. Astra International towards the whole community and village government. 2) knowing the impact of the CSR program of PT. Astra International towards the welfare of society. This type of research is descriptive qualitative. Data were obtained by conducting in-depth interviews with KBA managers, village heads, and communities receiving CSR programs. Test the validity of the data using technical triangulation and source triangulation. The results showed that the implementation of CSR consisted of Stage I, Stage II, Stage III, Stage IV, Stage V and 4 pillars consisting of: pillars of education, pillars of health, pillars of environment and pillars of entrepreneurship and evaluation; evaluation and rewards. In the implementation, it has fulfilled the triple bottom line concept. CSR PT. Astra International has a positive impact on people's welfare.